Investigating Teacher-Learner Interaction in EFL Classes a Basic Level of Learning - Qassim, Asmaa’ Y. (Humanities Journal of University of Zakho, 2017)
The current research aims at identifying the impact of teacher behavior on teacher-learner interaction in English language at the basic instruction level. The population consists of all male pupils in basic stage instruction within Kurdistan Region-Duhok city-Directorate of education, during the academic year (2013-2014). The sample for the study has been randomly chosen from the basic instruction – level 8. It consists of (32) pupils, sixteen forming the experimental group which has been taught by using Flanders Decimal System of behavior teacher-learner interaction (it has been prepared by the researcher depending on the source and other previous studies and researches so as to test the hypotheses of the current study. It has also been made valid through its presentation to a panel of experts, while the reliability factor has been computed by using the re-test method. On the other hand, sixteen pupils formed the control group which has been taught by using the Recommended Method by the Ministry of Education (henceforth RM). The t-test has been used for the equivalence of groups. Moreover, the researcher has used the tape recorder to access to the patterns of verbal interaction inside the classroom. The achievement test is the research tool for gaining the results of the experiment after being made valid and reliable. The findings show that teachers of English can make use of the given time in the class more successfully if they focus on encouraging learners (pupils) and accepting their ideas. Additionally, there is a limited influence of the variable related to the period of teaching service and place of graduation on the patterns of interaction inside the classroom as it has affected the percentage of the teacher’s instant questions. Thus, it showed teacher of English is the most effective strategy in teacher-learner interaction. The research ends with some recommendations and suggestions depending on the findings of the study